Wind Tunnel Testing of Airfoils for Wind Turbine Applications. Issue 6 (December 2015) - Kuester, Matthew S.; Brown, Kenneth; Meyers, Timothy; Intaratep, Nanyaporn; Borgoltz, Aurélien; Devenport, William J.
Accurate wind tunnel measurements of the lift and drag of airfoil sections are critical for the design and performance evaluation of wind turbine blades. As blades continue to increase in size, the demand for highly accurate wind tunnel results at progressively larger Reynolds numbers has also increased. Performing these wind tunnel measurements requires precise experimental control, and three challenges for these measurements are model surface quality, pressure tap effects, and model deflections under aerodynamic loading. These challenges were systematically studied in the Virginia Tech Stability Wind Tunnel using a DU96-W-180 airfoil geometry at a chord Reynolds number (Rec ) of 3.0 × 10 6 . Naphthalene sublimation showed turbulent wedges caused by surface imperfections; removing these imperfections increased the lift curve slope by 3%. Pressure tap diameter effects were investigated by placing taps of varying size at the same chord location on the airfoil. These measurements showed a steady pressure bias correlated to tap diameter when making measurements in turbulent boundary layers, and naphthalene visualizations showed a turbulent wedge created by pressure taps at the leading edge. Finally, laser distance sensors were used to measure model deflections/rotations under aerodynamic loading, improving upon the traditional angle of attack measurement. Addressing these challenges has improved the accuracy of lift measurements in the Stability Wind Tunnel and emphasized the need for precise experimental controls when performing these types of wind tunnel measurements.